Blind channel estimation with data from the INTIMATE'96 sea trial - Martins, N. (2014)
Blind multipath channel estimation is studied by time-frequency (TF) analysis. For a linear frequency modulated source, the technique is based on its instantaneous frequency estimation, followed by an approximate formulation of matched- ltering. Tests concern at-sea recorded data during the INTIMATE '96 experiment.